The Influence Of Korean Dramas On The Perception Of Korean Girls' Beauty Standards Among International Students - Permata Tania Nareswari, Agatha; Kusuma Fajar Mahardika, Satria (International Journal of Educational Research & Social Sciences, 2024)
Hallyu Wave, mainly known as Korean Wave from South Korea, has been spread out all over the world. This term is used to describe the popularity of Korean popular cultures in common. One of the Korean popular cultures that gain much attention in society around the world is their dramas. Korean dramas play an essential role in spreading the perception of girls' beauty standards. Therefore, this research aims to find out the influence of Korean dramas exposure that includes three variables, namely frequency, duration, and attention to the perception of Korean girls' beauty standards among international students. The population was from 8,275 international students pursuing bachelor's degrees in Sogang University, South Korea in Academic Year 2020/2021. According to the Slovin technique and purposive sampling, the research sample consisted of 100 international students that were divided into two different groups, Asian students and non-Asian students. Multiple linear regression was used to analyze the data. The results show that there was no individual influence between frequency, duration, and attention to Korean dramas exposure and the perception of Korean girls' beauty standards among Asian students. However, there was a negative influence between the duration of Korean dramas exposure and the perception of Korean girls' beauty standards among non-Asian students. Overall, the results show that frequency, duration, and attention to Korean dramas exposure did not influence the perception of Korean girls' beauty standards among Asian and non-Asian students.